ETHICAL KNOWLEDGE AND RESPONSIBLE INVESTMENT DECISION: A STUDY OF UNDERGRADUATE STUDENTS - Dermawan, Dicky; Nainggolan, Yunieta Anny (Journal of Business and Management, 2018)
Abstract. In the current investment boom, there is an increase in the number of demand from certain who considered not only that their investments are profitable, but they also meet certain non-financial criteria. From the available literature, it appears that there is a lot of disagreement among investors, firms, NGOs, and academicians about what ‘ethical investment’ is. It has been widely observed in many studies that financial motives encourage investment decision with an intensity much greater than the moral values that they may have. Socially Responsible Investment (SRI) has emerged as an important issue and drawn the attention of a large number of investors. These investors seem to be guided by a sense of moral duty to balance the pursuit of wealth with ethical or environmental concern. Business school has some responsibility for developing students’ ability to discover and apply values that can improve the future of our world. School of Business and Management, Institut Teknologi Bandung (SBM ITB) as a business school has critical roles in order to prepare leaders to make financial successful and driven by ethical values since ethical knowledge found as foundation of responsible investment. However, the factors that lead the student to invest socially responsible are not well understood, especially in SBM ITB. This study aims to analyze the investment pattern of the student towards the firms engaged in manufacturing ethical and unethical practices across the different demographics factors and to find out the factors that significantly affect ethical investment decision. The primary data gathered by distributing a survey through online questionnaire. The total numbers of respondents in this research are 100 respondents. For the analysis technique, this study performed descriptive, ANOVA, ordinary least squares regression, and logistic regression. Findings show that 69% of SBM ITB undergraduate students consider to invest socially responsible. The study found that class or batch and gender significantly affect ethical investment decision. A group of Female students with longest years of study tended to make ethical decision than younger years of study and male students.Keywords: Ethical Investment; Socially Responsible Investing; Financial Investment Decision; Behavior Finance